PENGARUH PRODUCT QUALITY, BRAND IDENTITY, PRICING STRATEGY, DAN PROMOTION TERHADAP PURCHASING DECISION (Jurnal Ekobis : Ekonomi Bisnis & Manajemen, 2023)
ABSTRACT Some MSME businesses experience problems in their marketing strategies due to limitations to meet market demand. Marketing strategies in MSME businesses can be created by paying attention to several variables including, product quality, brand identity, pricing strategy, and promotion in accordance with market share. Some of these variables can affect purchasing decisions made by consumers. This research was conducted on the Kecap Cap Jago MSME business in Pangandaran which experienced the same problem. The purpose of this study is to analyze each variable of product quality, brand identity, pricing strategy, and promotion toward purchasing decisions. The sampling technique uses purposive sampling with 120 respondents. The research method used is a quantitative approach with Structural Equation Modeling (SEM). The hypothetical results show that product quality and pricing strategy have a significant effect on purchasing decisions. While brand identity and promotion do not have a significant effect on purchasing decisions. This research implies that Kecap Jago MSMEs must improve brand identity and promotion in order to attract more consumers to make purchasing decisions. In addition, Kecap Cap Jago MSMEs must maintain quality and price strategies so that consumers still choose Kecap Cap Jago as their main choice.